Detection of protective level of inactivated vaccine against Avian mycoplasmosis in experiment on chickens - Обуховська, О. В. (Scientific Progress & Innovations, 2013)
The protective properties of the experimental series of inactivated vaccine against Avian mycoplasmosis was studied in the experiment on chickens. It is shown that twice intramuscular immunization provides 100 % protection of the birds from clinical manifestations of the disease and 95 % of the birds from infection by M. gallisepticum S6.